MOST EFFECTIVE CUSTOMER ACQUISITION STRATEGIES FOR HEALTHCARE E-COMMERCE STARTUP - Bhuvan Deepak Chada (International Journal of Modern Agriculture, 2020)
In this research, the idea is to find what strategies can be used by the companies in the E- Commerce market to make sure that the healthcare products would attract more customers. A review of literature established the themes that are prominent in this research. Following on the literature review, a research activity was designed to gain more knowledge about the topic. The participants of the research activity are the people who have professional knowledge regarding the strategies of sale.